The Freestyle Valve in Severe Necrotizing Aortic Root Endocarditis: Comorbidity Upon Outcome - Hansen, Lorenz; Ozga, Ann-Kathrin; Klusmeier, Michael; Hillebrand, Mathias; Tulun, Aysun; Pannek, Nora; Rieß, Friedrich-Christian (The Thoracic and Cardiovascular Surgeon, 2021)
Background Treatment of severe necrotizing aortic root endocarditis (SNARE) carries a substantial perioperative risk. As an alternative to homografts, we assessed short-term outcome and future prognosis in patients undergoing root replacement using the Freestyle valve.Methods Between 2000 and 2018, a total of 45 patients (mean age 70.9 ± 8.3 years, 66% men) underwent aortic root replacement for SNARE using the Freestyle valve. Mean Society of Thoracic Surgeons mortality score and EuroScore II were 22.6% ± 17.1 and 29.3% ± 20.9, respectively. Prosthetic endocarditis was present in 70.1%, and aortic annulus patch repair was performed in 64% of the patients. Median follow-up was 3.6 years (range: 0.1–14.5) and was 100% complete.Results The 30-day mortality was 15.5%. During follow-up, there were no reoperations, while reinfection was suspected in one patient. Survival was significantly inferior to the general population with a standardized mortality ratio of 10.7 (95% confidence interval [CI]: 9.1–12.6) (p < 0.0001). In 30-day survivors and after correction for significant comorbidities in a Cox proportional hazards model, estimated survival probabilities at 1, 5, and 10 years were 98.7 (95% CI: 92.5–99.8%), 94.1 (77.9–98.5%), and 63.8 (28.4–85.2%). Estimated mean difference in survival probability was better for the general population after postoperative year 6, but within the 95% CI for no difference.Conclusion Use of the Freestyle valve is reliable solution for the most complex cases with a low rate of reinfection. Early mortality is substantial and caused by the patient's condition and severity of the infection. Excess late mortality can be attributed to patient-specific comorbidities.
Keywords: aortic valve and root; endocarditis; xenograft